Levetiracetam-induced Stevens–Johnson syndrome/toxic epidermalnecrolysis overlap: A fatal case report - Rajendran, Aravind Manoj Kumar; Deshmukh, Vinod S (Indian Journal of Case Reports, 2026)
Levetiracetam is a second-generation antiepileptic drug (AED) that is generally regarded as having a favorablesafety profile and a lower propensity for severe cutaneous adverse reactions (SCARs) than the aromatic AEDs such as carbamazepine, phenytoin, and lamotrigine. Nevertheless, rare and occasionally fatal SCARs, including Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN), have been reported with its use. We describe a 29-year-old female with hypertension, hypothyroidism in the past 3 years, and a 1-year history of a seizure disorder who developed painful oral mucosal ulceration followed by generalized erythematous and dusky macules with epidermal detachment 10 days after the initiation of levetiracetam. The extent of epidermal detachment was estimated at approximately 18% of the body surface area, placing the eruption within the SJS/TEN overlap spectrum. Causality assessment using the Naranjo Adverse Drug Reaction Probability Scale and the World Health Organization–Uppsala Monitoring Centre criteria categorized the reaction as probable. Despite immediate withdrawal of the offending drug, fluid and electrolyte resuscitation, meticulous wound care, and supportive intensive management, the patient developed secondary sepsis with multiorgan dysfunction and died. Although levetiracetam is considered comparatively safe, clinicians must remain vigilant for life-threatening cutaneous reactions. Early recognition, immediate withdrawal of the suspected agent, and prompt referral to a specialized burn or intensive care unit are critical determinants of outcome.